Dutch disease in the post-Soviet countries of Central and South-West Asia: How contagious is it? - Balazs Egert (Center for Economic Studies and ifo Institute (CESifo), 2013)
This study seeks to determine the extent to which the former communist states of Central and South-West Asia are infected by the Dutch Disease. We take a detailed look at the functioning of the transmission mechanism of the Dutch Disease, i.e. the chains that run from commodity prices to real output in manufacturing. We complement this with two econometric exercises. First, we estimate nominal and real exchange rate models to see whether commodity prices are correlated with the exchange rate. Second, we run growth equations to analyse the possible effects of commodity prices and the dependency of economic growth on natural resources.
Keywords: E31; F31; O11; P17; 330